Kewenangan Dan Tanggung Jawab Pemerintah Dalam Hukum Tatanegara - AR, Muhamad Habibullah; Anwar, Syaiful; Fauzi, Muhammad; Yani, Ahmad; Siswoyo, Siswoyo; Miranda, Miranda (Hutanasyah : Jurnal Hukum Tata Negara, 2025)
The authority and responsibility of the government from the perspective of constitutional law, focusing on the relationship between the two in creating an effective and just government. The authority of the government in constitutional law covers various fields, from policy making to management of state resources, which must be carried out by prioritizing the principles of democracy and human rights. The responsibility of the government, on the other hand, demands accountability in every action and decision taken to ensure that the interests of the people and the state are achieved without abuse of power. This study uses a normative approach by analyzing various regulations and relevant literature to explore the legal implications of the authority and responsibility of the government. The findings of this article indicate that a clear understanding of authority and responsibility within the framework of constitutional law is essential to realizing good governance and maintaining political and social stability. The government must always act in accordance with the law, be transparent, and accountable in exercising its authority in order to gain public trust and ensure justice and public welfare.